Parent Education for Dialogic Reading: Online and Face-to-Face Delivery Methods. Issue 3 (2nd July 2016) - Beschorner, Beth; Hutchison, Amy
ABSTRACT: This study explored the impact of a parent education program and the contextual factors that influenced the experiences of families in the program. Seventeen parents completed a 9-week, face-to-face program and 15 parents completed a similar online program. This study was designed as a multiple case study and utilized multimethods for data collection and analysis. An inductive approach was utilized for data analysis. Each parent-child dyad completed pre- and postintervention video recordings of shared storybook reading. The videos were analyzed using the Adult Child Interactive Reading Inventory and the Wilcoxon signed-rank test was used. Parents receiving either delivery method increased their use of dialogue while sharing storybooks. There were no significant differences between the online and face-to-face adult and children's use of dialogue. The contextual factors that influenced the online participants were online access and design and delivery of content. The contextual factors that influenced the face-to-face participants were engagement, time, and group dynamics.